2020
DOI: 10.1210/clinem/dgaa060
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA HUPCOS Promotes Follicular Fluid Androgen Excess in PCOS Patients via Aromatase Inhibition

Abstract: Context Androgen excess is a key feature of polycystic ovary syndrome (PCOS), but the underlying molecular mechanism remains unclear. Objective To determine the role and mechanism of novel long noncoding RNA (lncRNA) highly up-regulated in PCOS (HUPCOS) in the androgen excess of PCOS patients. Design The lncRNA expression profile in granulosa cells derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Although thousands of lncRNAs in human or other organisms have been identified by highthroughput sequencing technology, only a few of them are well characterized (Liu et al, 2018;Stojic et al, 2020). Notably, only several lncRNAs including lncRNA-Neat1 (Nakagawa et al, 2014), lncRNA-HUPCOS (Che et al, 2020), and lncRNA-PVT1 (Liu et al, 2020) have been reported to be involved in the regulation of ovarian functions, such as steroid hormone secretion and corpus luteum formation. However, the role of lncRNAs in regulating follicular development, GC state, and functions remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although thousands of lncRNAs in human or other organisms have been identified by highthroughput sequencing technology, only a few of them are well characterized (Liu et al, 2018;Stojic et al, 2020). Notably, only several lncRNAs including lncRNA-Neat1 (Nakagawa et al, 2014), lncRNA-HUPCOS (Che et al, 2020), and lncRNA-PVT1 (Liu et al, 2020) have been reported to be involved in the regulation of ovarian functions, such as steroid hormone secretion and corpus luteum formation. However, the role of lncRNAs in regulating follicular development, GC state, and functions remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RNA-binding protein with multiple splicing RBPMS was identified as a direct binding protein of HUPCOS. This study showed that a novel lncRNA, HUPCOS, mediated androgen excess in the follicular fluid of PCOS patients by inhibiting aromatase expression via interaction with RBPMS [53].…”
Section: Lncrna-hupcosmentioning
confidence: 81%
“…When androgen secretion is excessive, the high sensitivity of Gcs to FSH causes a large increase in AMH, and AMH in turn inhibits the effect of FSH on aromatase in follicles (106). Recently, che et al (107) found that the highly expressed lncRNA HUPcOS of granulosa cells in patients with PcOS can interact with RNA-binding protein with multiple splicing (RBPMS) and inhibit the expression of aromatase, thereby mediating the excess of androgen in the follicular fluid of PCOS patients Therefore, the decrease in the aromatase activity conversely helps maintain high androgen levels (102,107). In addition, CYP19A1 and A-Kinase anchor protein 95 (AKAP95) levels are significantly decreased in human luteinized Gcs of patients with PcOS.…”
Section: Changes In Aromatase Activity Of Gcs Induce Diseasesmentioning
confidence: 99%